Hubungan Gaya Kepemimpinan Transformasional dan Motivasi Kerja pada Karyawan di Perusahaan Daerah Air Minum (PDAM) Kota Salatiga - Dhiya Surya Salsabilla, Kr; Doddy Hendro Wibowo (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine the relationship between transformational leadership style and employee work motivation at the Salatiga City Regional Drinking Water Company (RDWC) This study used quantitative methods. The subjects in this study numbered 134 people, selected using a saturated sampling technique, where the entire study population was sampled. The data collection process was conducted using Pearson correlation. The results showed a positive and significant relationship between transformational leadership style and employee work motivation at the Salatiga City Regional Drinking Water Company (RDWC).